COMPARATIVE STUDY BETWEEN CLUSTERING TECHNIQUE AND MIND MAPPING TECHNIQUE TO IMPROVE STUDENTS’ WRITING ABILITY AT THE EIGHT GRADE OF SMPN 2 TOLITOLI - Diyenti Rusdin; Madelin Tabise (Jurnal Madako Education, 2020)
The objective of this research is to find out the significant difference between Clustering technique and Mind Mapping technique in improving students’ writing ability at the eight grade of SMPN 2 Tolitoli. It is a true-experimental research. It was conducted at eight grade of SMP Negeri 2 Tolitoli. The researcher gave a pre-test to measure the students’ previous ability in writing. Then, a post-test was to find out the students’ writing ability after given treatment which is the application of clustering and mind mapping technique. The researcher used SPSS 21 program to analyze the data collection. The result of data analysis showed that clustering technique and mind mapping technique gave a significance effect to the students in writing ability. The mean score of post test in mind mapping technique (71,00) was higher than the mean score of pre-test (32,33). And the mean score of post-test in clustering technique (68,10) was higher than the mean score of pre-test (34,76). Although, the improvement in mind mapping technique was more effective than clustering technique  but the testing of hypothesis showed that the value of tcount was lower than ttable (0,717≤2,021). Hence, there was no a significance difference in writing achievement score between students were taught to using clustering technique and mind mapping technique at the eight grade of SMPN 2 Tolitoli.Key words: Comparative, mind mapping technique, clustering technique, writing ability.